Digital technology development and systemic financial risks: Evidence from 22 countries - Xu Haoran; Miao Wenlong; Zhang Siyu (Borsa Istanbul Review)
This study evaluates how digital technology development affects systemic financial risks in various countries. We employ cross-country sample data from over 5000 financial institutions in 22 countries from 2013 to 2021. The results reveal that the rapid growth of digital technology increases the systemic financial risks of various countries; this increase is related to disparities in the digital technology development stages and financial system structures. Furthermore, this study investigates the emotional contagion, complex financial linkage, and valuation inhibition effects on digital technology development's impact on systemic financial risks. Heterogeneity analysis shows that in countries with high levels of digital technology development and market-oriented financial systems, digital technology's effect on intensifying systemic financial risks is more significant.